Preventing venous thromboembolism at a district hospital: a quality improvement study - Bernhard G. Beutel; Louis S. Jenkins (South African Family Practice)
Background: Pulmonary embolism (PE) is the most common preventable cause of hospital deaths, and almost all hospitalised patients have at least one risk factor for venous thromboembolism (VTE). Despite the availability of highly effective thromboprophylaxis in preventing VTE, numerous studies worldwide have demonstrated its under-utilisation. The aim of this study was to review and improve the utilisation of thromboprophylaxis in the prevention of VTE in hospitalised patients at Oudtshoorn district hospital, and to make recommendations to the Western Cape Department of Health on how to improve the quality of care for patients at risk for VTE at district hospitals.